2003
DOI: 10.1002/j.0022-0337.2003.67.5.tb03654.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Computer‐Aided, Self‐Instructional Programs in Dental Education: A Systematic Review of the Literature

Abstract: Computer-aided learning (CAL), self-instructional programs provide an accessible, interactive, and flexible way of presenting curriculum material. In order to assess the effectiveness of CAL programs in dental education, a systematic review of the published literature comparing CAL with other teaching methods was performed. A systematic search of the published literature was performed. Articles formally assessed for inclusion had to meet the following criteria: randomized controlled trials comparing CAL with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
118
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 36 publications
9
118
2
3
Order By: Relevance
“…A systematic review of the effectiveness of computer-aided, self-instructional programs in dental education has revealed disparate outcomes, with some studies finding no difference between CAL and other learning strategies, and others indicating the opposite thus that CAL provided a significant advantage in terms of knowledge gain. 7 This is an important issue that needs to be explored in future studies with regards to the use of digital assessment tools as a self directed learning tool. Will the use of these devices indeed increase the technical performance of students?…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the effectiveness of computer-aided, self-instructional programs in dental education has revealed disparate outcomes, with some studies finding no difference between CAL and other learning strategies, and others indicating the opposite thus that CAL provided a significant advantage in terms of knowledge gain. 7 This is an important issue that needs to be explored in future studies with regards to the use of digital assessment tools as a self directed learning tool. Will the use of these devices indeed increase the technical performance of students?…”
Section: Discussionmentioning
confidence: 99%
“…This paradox has been summarised in the statement that 'many innovative tools have emerged from education research but we are still struggling to determine how these tools can best be used in pursuit of our educational mission.' 22,23 A recent sur vey of electronic curriculum imple mentation at 66 North American dental schools found that e-curricu lum implementation in these schools was following a classic innovation pat tern, with a few institutions rapidly implementing while the majority made modifi cations slowly. 24 In the United Kingdom, a review of the attitudes of undergraduates and staff to the use of electronic learning found that e-teach ing was accepted more by students than by staff and that some departments were unwilling to put learning mate rial online, even if it was password pro tected.…”
Section: Barriers To Change In Dental Educationmentioning
confidence: 99%
“…The benefits of computer-assisted learning can be seen for example in self-paced and selfdirected learning and increased motivation [15]. The effectiveness of computer-aided programs in dental education have also been analyzed [16]. Those authors concluded that computer-assisted learning can provide innovative and interactive ways of presenting material, and, therefore, should be used with conventional teaching or as a mean of self-instruction that can elicit a positive response from students and can motivate them.…”
Section: Introductionmentioning
confidence: 99%